Improving the Methodology for Developing Future Teachers Digital Competence - Xujakulov Sherzod Amankulovich (Researchparks Publishing, 2026)
This article examines the pedagogical mechanisms for developing the digital competence of future teachers and evaluates their effectiveness. As the methodological framework of the study, the internationally recognized TPACK (Technological Pedagogical Content Knowledge) model was adapted and applied to the national higher education system. The experimental research was conducted at Samarkand State Pedagogical Institute, Navoi State University, and Kokand State University, focusing on students' adaptation to the digital environment and self-study skills. Statistical analysis revealed that the performance level in the experimental groups was 10.11% higher than in the control groups, scientifically proving the effectiveness of the developed pedagogical methodology.